Prognostic Value of SERPINA1 as a Biomarker for Poor Survival of Gliomas - Nai-Jui Cheng; Hao-Yuan Hung; Tzu-Tsao Chung; Wen-Shin Song; Kun-Ting Hong; Dueng-Yuan Hueng (Journal of Medical Sciences, 2025)
Background: Glioma is a primary brain tumor known for its aggressive behavior and poor prognosis. Alpha-1 antitrypsin (SERPINA1) is a protein with a crucial role in regulating inflammatory processes in the body. Prior research has shown that SERPINA1 enhances the invasive and metastatic capabilities of several cancer types, including lung, breast, and colorectal cancer. Notably, SERPINA1 has also been found to be overexpressed in human gliomas. Considering the poor prognosis and high mortality rate of glioma, there is an urgent demand for more reliable biomarkers to assess its outcome. Aim: This study aims to explore the potential role of SERPINA1 in glioma by leveraging the Gene Expression Profiling Interactive Analysis (GEPIA), Chinese Glioma Genome Atlas (CGGA), and Gene Expression Omnibus (GEO) databases to evaluate its viability as a prognostic biomarker for glioma. Methods: We analyzed GEPIA, CGGA, and GEO databases to assess SERPINA1 mRNA expression in glioma and its link to overall survival. The CGGA databases were utilized to investigate the interactions between SERPINA1 and proteins such as proteinase 3, elastase neutrophil expressed (ELANE), PRSS3P2, KLK3, and calnexin. Results: This study indicated that SERPINA1 mRNA is significantly overexpressed in glioma, with this overexpression strongly linked to poorer overall survival. In addition, analysis at the single-cell level revealed a significantly elevated expression of SERPINA1 in myeloid cells. Evaluation of the CGGA database further showed a strong correlation between SERPINA1 and ELANE expression in glioma. Conclusion: Our findings suggest that SERPINA1 is positively associated with poor survival in glioma and may serve as a valuable biomarker for predicting survival outcomes in glioma patients.